Risk of refeeding syndrome. Case report - Adriana Giraldo Villa (Case Reports)
Introduction: Refeeding syndrome is an acute metabolic disorder that occurs during nutritional repletion. Although it has been known for years, the early detection of risk factors for its onset and the implementation of measures to prevent it are not common in nutritional care.